Simulação de dispersão de poluentes na atmosfera pela técnica de transformada integral para uma fonte arbitrária - Schuch, Daniel Andrade (2011)
The present work shows an analytical solution for the two-dimensional advectiondiffusion equation applied to the dispersion of pollutants released in the Atmospheric Boundary layer. The problem is solved by the combination of the Laplace Transform and GILTT (Generalized Integral Laplace Transform Technique) techniques. This solution has no limitations regarding the turbulent diffusion coefficients and wind profile depending on the height. An arbitrary source is added to the advectiondiffusion equation to model the process of first order chemical reactions. The concentration fields obtained computationally are compared with experimental data available in the literature.